DJ-1 is involved in the multidrug resistance of SGC7901 gastric cancer cells through PTEN/PI3K/Akt/Nrf2 pathway. (30th October 2020) - Qiu, Lejia; Ma, Zhaoxia; Li, Xiaoran; Deng, Yizhang; Duan, Guangling; Zhao, L e; Xu, Xingwang; Xiao, Lin; Liu, Haoyue; Zhu, Zhengming; Chen, Heping
Abstract: Gastric cancer is a common malignancy worldwide. The occurrence of multidrug resistance (MDR) is the major obstacle for effective gastric cancer chemotherapy. In this study, the in-depth molecular mechanism of the DJ-1-induced MDR in SGC7901 gastric cancer cells was investigated. The results showed that DJ-1 expression level was higher in MDR variant SGC7901/VCR cells than that in its parental SGC7901 cells. Moreover, DJ-1 overexpression conferred the MDR phenotype to SGC7901 cells, while DJ-1 knockdown in SGC7901/VCR cells induced re-sensitization to adriamycin, vincristine, cisplatin, and 5-fluorouracil. These results suggested that DJ-1 mediated the development of MDR in SGC7901 gastric cancer cells. Importantly, further data revealed that the activation of PI3k/Akt and Nrf2 signaling pathway were required for the DJ-1-induced MDR phenotype in SGC7901 gastric cancer cells. Meanwhile, we found that PI3k/Akt pathway was activated probably through DJ-1 directly binding to and negatively regulating PTEN, consequently resulting in Nrf2 phosphorylation and activation, and thereby inducing Nrf2-dependent P-glycoprotein (P-gp) and Bcl-2 expressions in the DJ-1-mediated MDR of SGC7901 gastric cancer cells. Overall, these results revealed that activating PTEN/PI3K/Akt/Nrf2 pathway and subsequently upregulating P-gp and Bcl-2 expression could be a critical mechanism by which DJ-1 mediates the development of MDR in SGC7901 gastric cancer cells. The new findings may be helpful for understanding the mechanisms of MDR in gastric cancer cells, prompting its further investigation as a molecular target to overcome MDR.